2018
DOI: 10.1186/s12876-018-0813-z
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection under general anesthesia for superficial esophageal squamous cell carcinoma is associated with better clinical outcomes

Abstract: BackgroundEndoscopic submucosal dissection (ESD) has been widely accepted for treating superficial esophageal squamous cell carcinoma (SESCC). The aim of this study was to evaluate the efficacy and safety of ESD for SESCC and the effect of different sedation methods on their clinical outcomes.MethodsWe retrospectively analyzed a total of 169 patients (175 lesions) who underwent ESD for SESCC at Samsung Medical Center, Seoul, South Korea. Short-term and long-term clinical outcomes were evaluated and compared ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 43 publications
(47 reference statements)
0
54
0
Order By: Relevance
“…In those studies, no death due to esophageal cancer occurred during a long-term follow-up of patients who underwent endoscopic resection of SESCC with invasion up to the mucosa. 71,72 There are conflicting research results regarding the association between undifferentiated esophageal cancer and the risk of lymph node metastasis, indicating that undifferentiated esophageal cancer cannot be yet used as an absolute contraindication of endoscopic resection for SESCC.…”
Section: Statement E6: We Recommend Oral Steroid or Local Steroid Injmentioning
confidence: 99%
“…In those studies, no death due to esophageal cancer occurred during a long-term follow-up of patients who underwent endoscopic resection of SESCC with invasion up to the mucosa. 71,72 There are conflicting research results regarding the association between undifferentiated esophageal cancer and the risk of lymph node metastasis, indicating that undifferentiated esophageal cancer cannot be yet used as an absolute contraindication of endoscopic resection for SESCC.…”
Section: Statement E6: We Recommend Oral Steroid or Local Steroid Injmentioning
confidence: 99%
“…To develop the hypothesis for our study, we presumed that ESD performed under GA would have better therapeutic outcomes and fewer adverse events than those not performed under GA, because GA would prevent patients from demonstrating even subtle movements during the procedure. As noted previously, previous study results involving esophageal or gastric ESD indicated that GA decreases the risk of adverse events, compared with traditional sedation administered by endoscopists [2,17]. Further, a previous study of esophageal ESD procedures, conducted at our institute, showed that the en-bloc resection rate was signi cantly higher and perforation rate was signi cantly lower in patients receiving GA than in those receiving traditional sedation; GA was shown to be a factor associated with achieving complete resection and minimizing perforations [17].…”
Section: Association Between Therapeutic Outcome and Anesthetic Modalitymentioning
confidence: 61%
“…As noted previously, previous study results involving esophageal or gastric ESD indicated that GA decreases the risk of adverse events, compared with traditional sedation administered by endoscopists [2,17]. Further, a previous study of esophageal ESD procedures, conducted at our institute, showed that the en-bloc resection rate was signi cantly higher and perforation rate was signi cantly lower in patients receiving GA than in those receiving traditional sedation; GA was shown to be a factor associated with achieving complete resection and minimizing perforations [17]. Despite only a few studies comparing GA and MAC, MAC has been shown to provide more clinical bene ts than GA. One retrospective study compared endovascular angioplasty outcomes, in patients with aortoiliac disease, according to the intra-operative use of GA or MAC.…”
Section: Association Between Therapeutic Outcome and Anesthetic Modalitymentioning
confidence: 61%
“…20 Second, all ESDs were conducted under general anesthesia and performed by only one of three doctors who had 10 years' experience in endoscopic operation, and who collectively have performed an average of 30 ESDs. Recently Song et al 21 reported that conscious sedation was an independent risk factor for incomplete resection, while general anesthesia improves the outcomes of esophageal ESD. Third, no patient in our cohort had pathologically confirmed lymphovascular involvement, and we excluded cases with positive margin, which are associated with cancer recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%